2018
DOI: 10.1007/s00213-018-4992-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomic profiling of a ketamine and placebo crossover trial of major depressive disorder and healthy control subjects

Abstract: (R,S)-Ketamine produces rapid, robust, and sustained antidepressant effects in major depressive disorder. Specifically, its pharmacological efficacy in treatment refractory depression is considered a major breakthrough in the field. However, the mechanism of action of ketamine’s rapid effect remains to be determined. In order to identify pathways that are responsible for ketamine’s effect, a targeted metabolomic approach was carried out using a double-blind, placebo-controlled crossover design, with infusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 59 publications
4
67
0
Order By: Relevance
“…Rotroff and colleagues have found a negative association between the levels of ornithine and citrulline with changes in the Montgomery-Åsberg depression rating scale after treatment with ketamine 20 . In line with our findings, several studies have reported lower levels of citrulline in MDD patients compared to healthy controls 51,52 , while another reported lower levels of arginine in MDD patients compared to healthy controls 53 . Hence, a full analysis of these pathways is warranted in which measurements of more metabolites are covered.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Rotroff and colleagues have found a negative association between the levels of ornithine and citrulline with changes in the Montgomery-Åsberg depression rating scale after treatment with ketamine 20 . In line with our findings, several studies have reported lower levels of citrulline in MDD patients compared to healthy controls 51,52 , while another reported lower levels of arginine in MDD patients compared to healthy controls 53 . Hence, a full analysis of these pathways is warranted in which measurements of more metabolites are covered.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, after 8 weeks of SSRI treatment, the short-chain acylcarnitinesspecifically propionyl carnitine (C3), butyryl/isobutyryl carnitine (C4) and isovaleryl/methylbutyryl carnitine (C5)were significantly increased while acetyl carnitine (C2) levels were decreased. Several studies have previously reported perturbations in C2 after antidepressant treatment in depressed patients 20,32,52 . In a rat model of depression, incomplete βoxidation of fatty acids has been associated with elevated medium-and long-chain acylcarnitines (Chen, Wei et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations